A brief primary care intervention to reduce fear of movement in chronic low back pain patients. Issue 1 (25th September 2014) - Guck, Thomas P; Burke, Raymond V; Rainville, Christopher; Hill-Taylor, Dreylana; Wallace, Dustin P
Abstract: Fear avoidance model of chronic pain-based interventions are effective, but have not been successfully implemented into primary care. It was hypothesized that speed walking times and key measures of the fear avoidance model would improve following the brief intervention delivered in primary care. A brief primary care-based intervention (PCB) that included a single educational session, speed walking (an in vivo desensitization exposure task), and visual performance feedback was designed to reduce fear avoidance beliefs and improve function in 4 patients with chronic low back pain. A multiple baseline across subjects with a changing criterion design indicated that speed walking times improved from baseline only after the PCB intervention was delivered. Six fear avoidance model outcome measures improved from baseline to end of study and five of six outcome measures improved from end of study to follow-up. This study provides evidence for the efficacy of a brief PCB fear avoidance intervention that was successfully implemented into a busy clinic for the treatment of chronic pain.